Development and application of a TaqMan-MGB probe-based quantitative real-time polymerase chain reaction assay for the rapid detection of Dictyocaulus filaria - Gao, Zheng-qin; Xing, Jin (Frontiers in Veterinary Science, 2025)
Lungworm disease caused by Dictyocaulus filaria is an infectious condition affecting sheep and goats worldwide in recent years. It causes significant economic losses and is considered a potential public health threat. To date, there have been few studies on Dictyocaulus filaria. Its pathogenic mechanism is still unclear, and there are no effective vaccines or drugs available for the prevention and control of the disease. Therefore, it is essential to develop a rapid and reliable molecular diagnostic method to facilitate the study of this novel parasite. In this study, we developed a TaqMan-minor groove binder (MGB) probe-based quantitative real-time polymerase chain reaction (qPCR) for the rapid detection of Dictyocaulus filaria for the first time. Specific primers and a TaqMan-MGB probe were designed targeting the internal transcribed spacer 2 (ITS2) region of Dictyocaulus filaria. The assay showed a strong specificity for detecting Dictyocaulus filaria, and had no cross-reactivity with other control pathogenic parasites. It also exhibited high sensitivity, with both the lower limit of quantification (LLOQ) and the limit of detection (LOD) determined to be 1.5 copies per reaction. The assay exhibited excellent repeatability and reproducibility, with an intra-assay coefficient of variation (CV) of 0.11–0.58% and an inter-assay CV of 0.33–2.19%. Finally, the developed TaqMan-MGB probe-based qPCR was used to detect 200 clinical samples. The results indicated that the positive detection rate of Dictyocaulus filaria was 3.5% (7/200) for Dictyocaulus filaria, and this finding showed good consistency with conventional PCR. The developed TaqMan-MGB probe-based qPCR assay offers several advantages, including high sensitivity, strong specificity, high throughput, speed, convenience, and cost-effectiveness. It is of great significance for safeguarding animal quality and protecting human health.